Testosterone response to competition in males is unrelated to opponent familiarity or threat appraisal - Oliveira, Gonçalo A.; Uceda, Sara; Oliveira, Tânia F.; Fernandes, Alexandre C.; Garcia-Marques, Teresa; Oliveira, Rui F. (Frontiers in Psychology, 2014)
It has been proposed in the literature that the Testosterone (T) response to competition in humans may be modulated by cognitive variables.In a previous experiment with a female sample we have reported that opponent familiarity and threat appraisal moderated the Testosterone (T) response to competition in women. With this experiment we aim to investigate if these variables have the same impact on males T response to competition, extending the previous findings in our lab. Forty male participants (twenty dyads) were recruited to engage in a same sex, face to face competition using the Number Tracking Test as a competitive task. Levels of T, Cortisol (C) and Dehydroepiandrosterone (DHEA) were measured before and twenty minutes after the competition. Results show that losers report higher levels of threat than winners and increased their T levels after the competition, however this T change was not predicted by opponent familiarity or threat appraisal. No variation was detected for C and DHEA levels. These findings suggest that there could be sex differences for the moderators/mediators of the T response to competition in humans.